Ethnoscience in Learning Science: A Systematic Literature Review - Raudhatul Jannah; Festiyed Festiyed; Yerimadesi Yerimadesi; Lufri Lufri; Sandijal Putra (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This study aims to determine the trend of ethnoscience development research in science learning in Indonesia. As classified as the qualitative research, this study used a content analysis approach. A systematic literature review technique was done to analyze the ethnoscience approach in science learning, used 73 reviewed articles, from 2017 to March 2022. The results shows: (a) Integrated research topics is the most dominant ethnoscience approach used to develop learning Modules with 4D research designs,(b) Learning outcomes are integrated with ethnoscience, especially for scientific literacy, critical thinking skill, creative thinking skill and problem-solving. (c). The ethnoscience-integrated learning model is dominated by project-based learning and discovery learning models at the high school level with biology subjects. The ethnoscience approach in science learning  preservice the local culture as the attempt to develope the students’ scientific literacy  beside reintroducing the culture.